How attachment affects users’ continued use intention of tourism mobile platform: A user experience perspective - Xiang, Guopeng; Chen, Qian; Li, Qiucheng (Frontiers in Psychology, 2022)
Continued use intention of customers is a critical factor in the development of tourism mobile platforms (TMP), which reflects the degree of users’ attachment to the platforms. However, existing research in this field intends to investigate users’ attachment to a TMP by focusing on the overall cognitive satisfaction of the users, which deviates from the “cognition-affect” framework in psychology. Following the stimulus–organism–response(S-O-R) framework, this paper draws upon the attachment theory and the user experience theory, and proposes a model depicting how service experience of TMP affects users’ intention to keep using the TMP through the mediation effect of platform attachment. The empirical results (N=276) showed that functional experience and social experience positively affect TMP users’ development of platform attachment (i.e., platform dependence and platform identity), which in turn enhance their intention to continuously obtain and provide tourism information via the TMP. This study expands the research on the continued use of TMP from an attachment perspective and contributes to the field in both theoretical and practical levels.